DURASI MENDERITA DM MEMENGARUHI KONTROL GLIKEMIK JANGKA PANJANG YANG DIUKUR MELALUI HbA1c PADA PASIEN DIABETES MELITUS TIPE 2 - Nurgajayanti, Cendi; Susilawati, Tri Nugraha; Wiboworini, Budiyanti (Poltekkes Kemenkes Bandung, 2024)
Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia due to abnormalities in insulin secretion or action. In West Java, the prevalence of DM reached 1.9%, with a significant increase in Tasikmalaya City, which recorded 7,436 cases in 2022. This study aimed to explore the relationship between individual characteristics, nutritional status, comorbidities, and duration of DM with HbA1c levels in type 2 diabetes patients at one of the private hospitals in Tasikmalaya City.This study evaluated medical records of 210 patients with type 2 DM. The Spearman's rank correlation test was used to analyse the relationships between variables and a p<0.05 was considered as statistically significant. The research design used is cross sectional with purposive sampling technique.The result showed there was a statistically significant relationship between the duration of illness and HbA1c levels (p = 0.001 and r = 0,072). However, the relationship between nutritional status or comorbidities and HbA1c levels were not statistically significant (p = 0.471 and 0.187, respectively), indicating no relationship between nutritional status and HbA1c levels. The study concluded there was no significant relationship between nutritional status and comorbidities with HbA1c levels. Namun, ada hubungan antara durasi penyakit dengan kadar HbA1c